From Expert Computational Knowledge to Interdisciplinary Communication - Eva Dokladalova; Rédha Hamouche; Rémy Kocik (Journal of Systemics, Cybernetics and Informatics)

(untitled)
In the contemporary landscape, the fields of cybernetics, artificial intelligence, and digital technology significantly impact society, reshaping production processes, decision-making frameworks, and human behaviors. Training engineers with transversal skills becomes imperative to navigate workflow complexities and communicate across these disciplines. We propose a new learning approach structured around expert prerequisites, integrating AI principles dedicated to Embedded Systems engineering track. Our module focuses on creating an autonomous driving vehicle using an autonomous robot kit, fostering interdisciplinary learning. Real-time demonstrations assess learning outcomes, emphasizing problem-solving skills. Inspired from recent evaluation concept of interdisciplinary assessment. Our evaluation criteria emphasize functionality, integrated idea defense, and written reports. The defense organization scheme fosters positive perceptions of interdisciplinary links.